Case report: Hilar metastasis of breast cancer: A single-center retrospective case-control study - Yang, Ruohan; Jia, Lin; Lv, Zheng; Cui, Jiuwei (Frontiers in Surgery, 2023)
Purpose: The lungs are a common metastatic organ in breast cancer, mainly due to blood metastasis. On imaging, most metastatic lesions show a peripheral round mass in the lung, occasionally with a hilar mass as the main manifestation, showing burr and lobulation signs. The purpose of this study was to investigate the clinical characteristics and prognosis of breast cancer patients with two different metastatic sites in the lung. Methods: We retrospectively analyzed patients admitted to the First Hospital of Jilin University between 2016 and 2021 who had been diagnosed with breast cancer lung metastases. Forty breast cancer patients with hilar metastases (HM) and 40 patients with peripheral lung metastases (PLM) were matched 1:1 using a pairing method. The clinical characteristics of patients with two different metastatic sites were compared using the chi-square test, Kaplan–Meier curve, and Cox proportional hazards model to analyze the patients’ prognosis. Results: The median follow-up time was 38 months (2–91 months). The median age of patients with HM was 56 years (25–75 years), and that of patients with PLM was 59 years (44–82 years). The median overall survival (mOS) was 27 months in the HM group and 42 months in the PLM group (p=0.001). The results of the Cox proportional hazards model showed that the histological grade (hazard ratio=2.741, 95% confidence interval 1.442–5.208, p=0.002) was a prognostic factor in the HM group. Conclusion: The number of young patients in the HM group was higher than that in the PLM group, with higher Ki-67 indexes and histological grades. Most patients had mediastinal lymph node metastasis, with shorter DFI and OS and poor prognosis.